The Impact of Storage Temperature on the Quality of Liquid Bath Cosmetic Products - Zięba, Małgorzata; Małysa, Anna; Klimaszewska, Emilia; Jagiełło, Olga; Gruszczyńska, Marlena; Gajowiak, Maja (Studia Oeconomica Posnaniensia, 2017)
Currently, cosmetic companies compete in creating innovative, increasingly inventive formulas. Simultaneously, the need to ensure proper product safety is increasing. There are legal regulations pertaining to the control of the quality of products. However, there are cases where the given product is not exposed to standard storage conditions. Due to the fact there is a risk that after a prolonged period of storage (e.g. at an increased temperature) there will be changes in the physicochemical properties of the given product. One should note that the fluctuations of temperature during transport or storage may significantly affect the destabilization of the finished cosmetic product. The factors influencing stability during the storage and transport of liquid bath cosmetic products were characterized. Particular consideration was given to the effects of increased temperature. As the determinants of the quality of bath products were designated: stability, viscosity, foam-forming properties and dissolubility. Also a sensory evaluation of shower gels was performed. After 3 months of storage, all the properties of the evaluated cosmetic products were changed. Increased temperature and storage time contribute to increased dynamic viscosity, formation of more abundant foam, increased foam stability indicator and increased time of dissolubility of the tested cosmetic products. They also have an impact on the selected sensory characteristics.